Appropriation: a fundamental pillar of Information Science - Elias Borges, Ellen Valotta [UNESP]; Almeida Junior, Oswaldo Francisco de [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2022)
Although appropriation of information is a key concept to understand the process of construction and meaning of information, it is noted that there is a lack of scientific studies in the field of Information Science that discuss this issue in more depth. Few studies are focus on the process, the elements and the result of appropriation. Based on this, this study aims to show the concept of appropriation of information based on a procedural and ideological perspective linked to Bakhtinian dilogism and his ideological sign. In this view, the concept of appropriation of information is presented as a construction process which results in materialization of information. Thus, the focus of this study is to understand what elements this process is made of and the relation between them, seeking to raise discussions focused on materialization of information. It is assumed that materialization takes place through the relationship among protoinformation particles, informational manifestation and informative consciousness. The constant interrelationship among these elements is a complex phenomenon which always takes place in relation to the other. From this perspective, it can be consider as an ideological and dialogical phenomenon. All in all, the construction of information depends on relations established between social subjects, which will result in a physical and non-physical materiality, which can be externalized or kept in the inner discourse.
Keywords: appropriation of information; materialization of information; protoinformation particles; informational manifestation; informative consciousness